Representing 9/11: Alejandro González Iñárritu’s short film in 11'09"01: September 11 - Marie-Christine CLEMENTE (E-REA)
In his 11'9"01: September 11 short film, Alejandro González Iñárritu responds to the oversaturated broadcast of the burning Twin Towers that characterises 9/11 by confronting his audience with a black screen that is haunted by sounds recorded around the world on September 11th, 2001. Two minutes into the film a first image finally appears on the screen and the viewer can glimpse the footage of a person falling down the Twin Towers. Similar flashes soon sporadically burst through the black screen and, as these visions have an extremely fleeting quality to them, room is left for the viewer to wonder whether he truly saw ‘jumpers’. Ungraspable by essence, the viewing of Iñarritu’s short film can be likened to a traumatic experience, which Cathy Caruth defines as ‘an event that … is experienced too soon, too unexpectedly, to be fully known and is therefore not available to consciousness until it imposes itself again, repeatedly, in the nightmares and repetitive actions of the survivor’ – the flashes of the ‘jumpers’ that pervade the short film bearing undeniable similarities to the return of the trauma.The paper shows how Iñárritu’s short film attempts to represent the unrepresentable dimension of 9/11. Stressing the fact that the film uses images of the ‘jumpers’ that were widely censored by the media in the aftermath of the 9/11 attacks, it analyses how the director transcends the sphere of representation by deconstructing the viewers’ habitual cinematic experience. As he explores the limits of sight and sound, Iñárritu produces an extremely unsettling viewing experience for his audience who is forced to adopt a type of perception that verges on the traumatic experience and his film can, to a certain extent, be read as staging the return of the trauma of the 9/11 attacks.